Academic Administration Affecting the Quality of Students in Basic Education Institutions Under Roi-Et Primary Educational Service Area Office 2 - Boonlert, Watchara; Khattiyasuwan, Saksit; Suriyasookprasert, Pichai; Laplay, Chalermwutpitak; Watanawong, Suwat (Rajapark Journal, 2024)
The objectives of this study were 1) to study academic administration in basic education institutions; 2) to compare academic administration in basic education institutions classified by the position of respondents; 3) to study the quality of learners in basic education institutions; and 4) to study academic administration that affects the quality of learners in basic education. It is quantitative research. The sample groups used in this research are school administrators, heads of academic administration, and teachers, totaling 362 people. The research instrument is a 5-level rating scale questionnaire with a confidence value of .95. Statistics used include percentage, mean, standard deviation, t-test, F-test, and one-way analysis of variance. When the differences were found, a pair test was performed using the Sheffe method. Pearson’s correlation coefficient and stepwise multiple regression analysis were also used. The results of the research were as follows: 1. It was found that in academic administration in basic education institutions, the overall level is very high. 2. Comparison of academic administration in basic education institutions, classified by the position of respondents, with an overall statistically significant difference at the .05 level. 3. The quality of learners in basic education institutions was found to be at the highest overall level. 4. Academic administration that affects the quality of learners in basic education institutions falls into 4 aspects: assessment, evaluation, and transfer of academic performance; curriculum development of educational institutions; supervision of education; and management of teaching and learning in educational institutions. It has a multiple correlation coefficient of .931 and can jointly explain the variance in student quality by 86.60%.